Numerical modelling of mixed flow impeller in stirred vessel - Mohiuddin, A. K. M.; Adeyemi, Nabeel A.; Jameel, Ahmed Tariq (2012)
Flow characteristics of a single mixed flow impeller in baffled and unbaffled vessel have been experimentally and numerically investigated at 600 rpm. The mean, radial and axial velocity components obtained using particle image velocimetry (PIV) were compared with three turbulence models (shear stress transport (sst) and Reynold's stress model (RSM))based on the Reynold’s averaging Navier-Stokes equation at two planes, above (x/R=0.46) and below (x/R = 0.38) the impeller. Numerical results of mean and axial velocity for the RSM turbulence model compared better to PIV below the impeller against other models in the baffled vessel. However, the axial and radial velocity components from the model compare well to PIV result at a distance away from the wall. Associated power number and energy of the impeller were also observed to be better predicted with the RSM, although at a higher computational cost. Trade-offs in using the RSM as a tool for simulation of the mixed flow impeller is suggested.